Distribusi dan Karakteristik Habitat Perkembangbiakan Larva Anopheles di Kabupaten Mandailing Natal, Sumatera Utara - Rusdiyah Rusdiyah; Imam Bachtiar; Abd. Gafur; Nayodi Permayasa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The high number of malaria cases in Mandailing Natal Regency, especially in the work area of the Siabu Health Center, shows that malaria eradication in Mandailing Natal Regency has not been carried out optimally, so it is necessary to have basic data on bionomic Anopheles mosquito vectors, especially larval breeding habitats. This study aims to identify potential breeding habitats for Anopheles larvae and their distribution through mapping using GPS. Data was collected by observing the potential habitat of Anopheles larvae and observing their physical and biological environment. Observation of Anopheles larvae was carried out using the larval scavenging method. The results showed that the types of Anopheles larvae breeding habitat in the working area of the Siabu Health Center were rice fields and ponds. The water temperature in the breeding habitat ranges from 27oC to 30oC. The entire breeding habitat of Anopheles larvae was exposed to direct sunlight. The salt levels in the breeding habitat was 0‰, with a pH of 7-8. The characteristics of the habitat found in the working area of the Siabu Health Center is a potential breeding ground for Anopheles larvaeKeywords: malaria; Anopheles; larvae; breeding habitat ABSTRAK Masih tingginya kasus malaria di Kabupaten Mandailing Natal terutama di wilayah kerja Puskesmas Siabu, memperlihatkan bahwa pemberantasan malaria di Kabupaten Mandailing Natal belum terlaksana secara optimal, sehingga  perlu adanya data dasar bionomik vektor nyamuk Anopheles, khususnya habitat perkembangbiakan larva. Penelitian ini bertujuan untuk mengidentifikasi habitat perkembangbiakan potensial larva Anopheles dan distribusinya melalui pemetaan dengan GPS. Pengumpulan data dilakukan dengan mengamati habitat potensial larva Anopheles dan mengamati lingkungan fisik dan biologinya. Pengamatan larva Anopheles dilakukan dengan metode pencidukan larva. Hasil penelitian menunjukkan bahwa jenis habitat perkembangbiakan larva Anopheles di wilayah kerja Puskesmas Siabu adalah sawah dan kolam. Suhu air pada habitat perkembangbiakan berkisar 27oC sampai 30oC. Seluruh habitat perkembangbiakan larva Anopheles terkena paparan sinar matahari langsung. Kadar garam pada habitat perkembangbiakan yaitu 0‰, dengan pH 7-8. Karakteristik habitat yang ditemukan di wilayah kerja Puskesmas Siabu adalah potensial untuk tempat perkembang biakan larva AnophelesKata kunci: malaria; Anopheles; larva; habitat perkembangbiakan